Integration of digital and traditional educational technologies in the process of forming musical-aural and creative competencies of higher education students - Teriaieva, Larisa (Educological discourse, 2026)
The article reveals educational and artistic-pedagogical aspects of integrating digital educational technologies into the process of forming musical-aural and creative competencies of higher education students. The expediency of using digital platforms, mobile applications, and online environments in the professional training of music art specialists is substantiated in the context of the digitalization of the educational space of higher education institutions. Based on the analysis of contemporary scientific approaches, the concepts and structure of musical-aural and creative competencies are specified within the framework of the competence-based educational paradigm. A model for their formation is proposed, which includes cognitive, operational-activity, creative-interpretative, and reflective-evaluative components. A pedagogical classification of digital music resources according to their functional purpose has been developed, which can be applied in the educational practice of higher education institutions, and the pedagogical conditions for their effective integration into the educational process have been determined. The article proposes a methodology that involves the step-by-step integration of digital technologies, ranging from aural training to students’ creative and productive activities. The conducted pedagogical experiment was based on the implementation of an authorial methodology for integrating digital educational technologies into the educational process. This methodology was realized in stages and provided for a systematic combination of traditional forms of music-theoretical instruction with digital platforms, mobile applications, and online music-oriented environments. The article also presents the organization and course of the experiment and analyzes the results of pedagogical observation, which demonstrated positive dynamics in the development of students’ aural and creative skills under the condition of systematic integration of traditional teaching forms with digital tools. Following the consistent use of digital educational technologies, an increase in the number of students with a high level of aural skill formation, an improvement in the quality of creative tasks, and a higher level of professional independence were recorded. Prospects for further research in the field of digital transformation of arts education are outlined.